Kemampuan Penyesuaian Diri Siswa Dengan Lingkungan Dapat Ditingkatkan Melalui Penerapan Metode Bermain Peran Mikro - Singgih, Singgih Prastawa (Global Education Journal, 2023)
This study aims to find out how the application of the micro role playing method can improve students' adjustment abilities to the environment in the RA Muslimat NU 100 Bediwetan Ponorogo Playgroup. In addition, this study also aims to find out how effective the application of the micro role playing method is in increasing students' adjustment to the environment in the RA Muslimat NU 100 Bediwetan Ponorogo Playgroup. The research that will be carried out by researchers is Classroom Action Research (CAR). Researchers will use an action research approach with a spiral model formulated by Stephen Kemmis in David Hopkins. The subjects of this study were students aged 3-4 years in the RA Muslimat NU Playgroup 100 Bediwetan Ponorogo, with a focus on class A2 which consisted of 14 students (9 boys and 5 girls). As for quantitative data analysis, there are other statistical analysis techniques such as regression analysis, factor analysis, and multivariate analysis. The micro role playing method is carried out with steps that have been formulated or can be carried out by the students themselves. The results of this work This method provides a stimulus for students to achieve goals, such as self-confidence, good interactions with others, empathy for friends, and a sense of discipline. The application of the micro role playing method can improve students' adjustment abilities to the environment in the group.